Characterization of a spotted fever group Rickettsia from Ixodes ricinus ticks in Sweden. - Nilsson, K (1997)
A spotted fever group rickettsia isolated from the common tick, Ixodes ricinus, was genetically characterized by PCR and genomic sequencing. This study was performed with nymphal and adult ticks collected in southern and central Sweden. I. ricinus is the only North European tick species of medical importance which is regularly collected from humans. No species of the genus Rickettsia has previously been found in Scandinavian ticks, nor has any case of domestic rickettsial infection in humans or animals been reported. According to the nucleotide sequencing, the present Rickettsia sp. belongs to the spotted fever group of rickettsiae. Ticks are the most common arthropod reservoirs and vectors of the rickettsiae of this group. Among 748 ticks investigated, 13 (1.7%) were positive for a Rickettsia sp. Borrelia burgdorferi was detected in 52 (7%) of the ticks, a prevalence similar to or somewhat lower than that previously been recorded in other Swedish studies. There was no evidence of ehrlichial or chlamydial DNA in these ticks. The Rickettsia sp. was further characterized by 16S ribosomal DNA (rDNA) sequencing and restriction fragment length polymorphism (RFLP). The 16S rDNA sequencing resulted in a sequence identical to that described for Rickettsia helvetica, but the pattern obtained with RFLP of the citrate synthetase gene diverged from previously known patterns. The rickettsial agent of one tick which was positive by PCR was confirmed by transmission electron microscopy. The morphology of this rickettsia was similar to that of the spotted fever and typhus group rickettsiae. This represents the first documented isolate of a Rickettsia sp. from Swedish ticks.